PARÁSITOS HELMINTOS EN Boa constrictor, Epicrates cenchria y Corallus caninus (Ophidia: Boidae) CRIADAS EN CAUTIVERIO - Sánchez P., Nofre (2004)
Fecal samples for the identification of helminthes were collected from three species of snakes (Boa contrictor “boa” or “mantona”, Epicrates cenchria “mantona roja” or “arco iris”, Corallus caninus “boa verde” or “boa esmeralda”) reared in captivity. The identified parasites, either through eggs or larva were: Kalicephalus sp., Ophiotaenia sp., Rhabdias sp., Ophidascaris sp., and Hymenolepis diminuta. The results indicated that 79% of adult female Boa constrictor and 46% of their offspring, 71% of E. cenchria and 70% of C. caninus were positive, either to single or multiple infections. These data showed that boas reared in captivity were highly parasitized with intestinal and pulmonary helminthes.